Cardiac mitochondria and arrhythmias - Brown, David A. (Oxford University Press, 2010)
Despite a high prevalence of sudden cardiac death throughout the world, the mechanisms that lead to ventricular arrhythmias are not fully understood. Over the last 20 years, a growing body of evidence indicates that cardiac mitochondria are involved in the genesis of arrhythmia. In this review, we have attempted to describe the role that mitochondria play in altering the heart's electrical function by introducing heterogeneity into the cardiac action potential. Specifically, we have focused on how the energetic status of the mitochondrial network can alter sarcolemmal potassium fluxes through ATP-sensitive potassium channels, creating a ‘metabolic sink’ for depolarizing wave-fronts and introducing conditions that favour catastrophic arrhythmia. Mechanisms by which mitochondria depolarize under conditions of oxidative stress are characterized, and the contributions of several mitochondrial ion channels to mitochondrial depolarization are presented. The inner membrane anion channel in particular opens upstream of other inner membrane channels during metabolic stress, and may be an effective target to prevent the metabolic oscillations that create action potential lability. Finally, we discuss therapeutic strategies that prevent arrhythmias by preserving mitochondrial membrane potential in the face of oxidative stress, supporting the notion that treatments aimed at cardiac mitochondria have significant potential in attenuating electrical dysfunction in the heart.